2014
DOI: 10.1016/j.jcomdis.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and perceptual correlates of faster-than-habitual speech produced by speakers with Parkinson's disease and multiple sclerosis

Abstract: Acoustic-perceptual characteristics of a faster-than-habitual rate (Fast condition) were examined for speakers with Parkinson's disease (PD) and Multiple Sclerosis (MS). Judgments of intelligibility for sentences produced at a habitual rate (Habitual condition) and at a faster-than-habitual rate (Fast condition) by 46 speakers with PD or MS as well as a group of 32 healthy speakers revealed that the Fast condition was, on average, associated with decreased intelligibility. However, some speakers' intelligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…To evaluate the effect of rate changes on variability outcomes, sentence productions of fast, habitual, and slow productions were analysed. Similar to findings reported in previous research [13, 46], when pooled across groups, speakers were able to implement a relative change in rate. With respect to implementing a slow rate, some variation was noted, with control speakers decreasing rate by 88%, while speakers with HD and AD decreased rate by 32% and 47%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…To evaluate the effect of rate changes on variability outcomes, sentence productions of fast, habitual, and slow productions were analysed. Similar to findings reported in previous research [13, 46], when pooled across groups, speakers were able to implement a relative change in rate. With respect to implementing a slow rate, some variation was noted, with control speakers decreasing rate by 88%, while speakers with HD and AD decreased rate by 32% and 47%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…There are additional reasons to be cautious of anticipating improvements in speech outcomes following rate reductions across the board for people with PD, however. One reason for this is that while some individuals may improve, several studies have reported that some talkers with PD do not exhibit increases in intelligibility when producing slower rates of speech, and some may even worsen ( Van Nuffelen et al, 2009 , 2010 ; Hall, 2013 ; Kuo et al, 2014 ; Fletcher et al, 2017 ; McAuliffe et al, 2017 ). Conversely, while faster speech is not likely to be a treatment target, a small body of literature has demonstrated that intentional increases in speech rate is not necessarily associated with what might be an expected decrease in intelligibility ( Kuo et al, 2014 ), and may even be associated with increases in naturalness or acceptability in some cases ( Logan et al, 2002 ; Dagenais et al, 2006 ; Sussman and Tjaden, 2012 ; Kim and Seong, 2015 ).…”
Section: Background and Rationalementioning
confidence: 99%
“…There are additional reasons to be cautious of anticipating improvements in speech outcomes following rate reductions across the board for people with PD, however. One reason for this is that while some individuals may improve, several studies have reported that some talkers with PD do not exhibit increases in intelligibility when producing slower rates of speech, and some may even worsen (Van Nuffelen et al, 2009, 2010Hall, 2013;Kuo et al, 2014;10.3389/fnhum.202410.3389/fnhum. .1331816 Fletcher et al, 2017McAuliffe et al, 2017).…”
Section: Rate Reductionmentioning
confidence: 99%
See 1 more Smart Citation